Artificial intelligence with python cookbook : proven recipes for applying ai algorithms and deep learning techniques using TensorFlow 2.x and PyTorch 1.6 - Auffarth, Ben (PACKT Publishing, 2020)
If you are looking to build next-generation AI solutions for work or even for your pet projects, you'll find this cookbook useful. With the help of easy-to-follow recipes, this book will take you through the advanced AI and machine learning approaches and algorithms that are required to build smart models for problem-solving.